Iris Meinen, and Nils Lehnert (Eds.). Öffnung–Schließung–Übertritte. Körperbilder in der deutschsprachigen Gegenwartsliteratur: Bielefeld: transcript Verlag, 2021, 294 pp. 40€ ISBN 978-3-8394-5680-4. - Jiang, Xiaohu (Germanic Review)
B Uta Schaffers b discusses two closely connected themes depicted in Clemens J. Setz's narratives, namely the body boundary and manipulation of others' bodies and wills. The conventional boundaries between body and spirit, between "Innen und Außen" (199) and those between bodies (200), are shattered in this novel. As Hermann states, this novel is a sharp critique of the Western idea of the duality of the body and spirit.